OUTCOME OF OPEN REPAIR VERSUS LAPAROSCOPIC SURGERY IN PATIENTS WITH DUODENAL ULCER PERFORATION (Journal of Medical & Health Sciences Review, 2025)
Background: Duodenal ulcer perforation is a life-threatening surgical emergency. With the advancement of minimally invasive techniques, laparoscopic repair has emerged as an alternative to conventional open surgery. However, comparative data on postoperative outcomes remains limited, especially in local contexts.Objective: To compare postoperative pain between laparoscopic and open surgical repair in patients with duodenal ulcer perforation.Methods: A randomized controlled trial was conducted at the Department of Surgery, Saidu Group of Teaching Hospital, Swat, over six months. Sixty patients with CT-confirmed duodenal ulcer perforation were enrolled and randomly assigned to laparoscopic (n=30) or open repair (n=30). Postoperative pain was assessed on postoperative day 3 using the Visual Analog Scale (VAS). Opioid consumption and time to return to normal activity were also recorded. Data were analyzed using IBM SPSS version 21. An independent sample t-test was used with a significance level of p